Effects of UV Radiation on Germination, Growth, Chlorophyll Content, and Fresh and Dry Weights of Brassica rapa L. and Eruca sativa L. - Hussan Ara Begum (17542320) (2021)
Due to the depletion in the ozone layer, solar UV radiation at the earth’s surface is increasing, impacting economically important plants. The current study assesses the effects of UV radiation on germination, growth, chlorophyll content and fresh and dry weight of Brassica rapa L. and Eruca sativa L. Some seeds of Brassica rapa L. and Eruca sativa L. were placed in petri plates, and were exposed to UV light for 30, 60 and 120 mins daily. The source of UV light was a UV box having a UV Tube. The UV exposure on the seeds reduced the germination percentage in both species. The germination percentage in control was recorded as 19.35%, while it was 18.65% in 30min and 19.00% in 120min exposures. Root and shoot growth of the seedlings was markedly reduced by increasing UV radiation. The shoot length was 2.40mm in control, 2.75mm in 30min, 1.50mm in 60min and 1.60mm in 120min of exposure to the UV light. The root length in control was 1.38mm, 0.90mm in 30min, 1.00mm in 60min and 1.17mm in 120min exposure. The UV irradiations affected the chlorophyll contents positively, and therefore, the total quantity of chlorophyll content increased, compared to the control. The chlorophyll content in the control was 6.90 (µmol m-2) of leaf area while treatment showed 8.08 (µmol m-2) in 30min, 8.01 (µmol m-2) in 60min and 10.01 (µmol m-2) in 120min exposure. In both species, fresh and dry weights were decreased, as compared to the control set. The fresh weight of the control was 0.85g, 0.65g in 30min, 0.78g in 60min and 0.61g in 120min exposure. The dry weight of the control was recorded to be 0.70g, 0.60g in 30min, 0.62g in 60min and 0.50g in 120min exposure. It was concluded that ultraviolet radiation decreased the radicle and plumule lengths in Brassica rapa and Eruca sativa while increasing their chlorophyll content. Other Information Published in: Sarhad Journal of Agriculture License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.17582/journal.sja/2021/37.3.1016.1024 Disclaimer: The University of Doha for Science and Technology replaced the now-former College of the North Atlantic-Qatar after an Amiri decision in 2022. UDST has become and first national applied University in Qatar; it is also second national University in the country.